2005
DOI: 10.1002/fld.1092
|View full text |Cite
|
Sign up to set email alerts
|

On the interplay between inertial and viscoelastic effects for the flow in weakly modulated channels

Abstract: SUMMARYThe ow inside a spatially modulated channel is examined for viscoelastic uids of the Oldroyd-B type. The lower wall is at and the upper wall is sinusoidally modulated. The modulation amplitude is assumed to be small. Thus, a regular perturbation expansion of the ow ÿeld coupled to a variable-step ÿnite-di erence scheme is used to solve the problem. Convergence and accuracy assessment against earlier experimental results indicate that there is a signiÿcant range of validity of the perturbation approach. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 48 publications
1
1
0
Order By: Relevance
“…The separation vortex has been observed in numerical simulations and experiments of both Newtonian and non-Newtonian fluid flows in wavy-walled channels [20,41]. The results we have obtained are consistent with those of the earlier studies in the point that both the convective and elastic terms influence on the flow pattern formation [47].…”
Section: Discussion and Concluding Remarkssupporting
confidence: 90%
“…The separation vortex has been observed in numerical simulations and experiments of both Newtonian and non-Newtonian fluid flows in wavy-walled channels [20,41]. The results we have obtained are consistent with those of the earlier studies in the point that both the convective and elastic terms influence on the flow pattern formation [47].…”
Section: Discussion and Concluding Remarkssupporting
confidence: 90%
“…It is observed that an increase in the wall amplitude leads to a larger vortex size and a smaller critical Reynolds number for the onset of back flow at either wall. In addition, it has been shown that the flow configuration in the converging-diverging nature of the periodically modulated channels provides an ideal setting for evaluating constitutive equations [38,40,41,[45][46][47] and for developing and testing the accuracy and efficiency of numerical methods in viscoelastic flow calculations [47][48][49]. Finite difference numerical solutions have been presented by Chiba et al [50] for the flow of dilute suspensions of rigid, high aspect-ratio fibres in Newtonian fluids flowing in an axisymmetric circular 4 to 1 contraction.…”
Section: Introductionmentioning
confidence: 97%